Pengaruh Pemberian Jus Buah Naga (Hylocorheus Polyhiruz) Terhadap Kadar Kolestrol Total Pada Lansia Di Posbindu Kebayoran Lama Utara Jakarta Selatan Tahun 2024 - Setiawati Hia; Emi Yuliza; Irma Herliana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Cholesterol is a fatty substance that circulates in the body which is produced by the liver and is very important for the body. Excessive cholesterol in the blood will first cause problems in the blood vessels and brain. The aim of this study was to determine the effect of giving dragon fruit juice on total cholesterol levels in the elderly at Posbindu Kebayoran Lama Utara, South Jakarta. The research method used a pre-experimental pre-post-test group design including administration of dragon fruit juice, analysis of measurements of total cholesterol levels before and after the intervention, and analysis of food cholesterol consumption. The Wilcoxon test results were chosen because the data did not meet the normality assumption. The p value resulting from the Wilcoxon test is 0.028, which is smaller than the significance level which is generally set at 0.05. This shows that the difference between total cholesterol levels before and after the intervention is statistically significant. The conclusion from the results of this research that has been carried out can be concluded that there is a significant difference between total cholesterol levels before and after the intervention (p<0.05).